Flavonoids-Rich Orthosiphon stamineus Extract as New Candidate for Angiotensin I-Converting Enzyme Inhibition: A Molecular Docking Study - Shafaei, Armaghan; Khan, Md Shamsuddin Sultan; Aisha, Abdalrahim F. A.; Majid, Amin Malik Shah Abdul; Hamdan, Mohammad Razak; Mordi, Mohd Nizam; Ismail, Zhari (MDPI, 2016)
This study aims to evaluate the in vitro angiotensin-converting enzyme (ACE) inhibition activity of different extracts of Orthosiphon stamineus (OS) leaves and their main flavonoids, namely rosmarinic acid (RA), sinensetin (SIN), eupatorin (EUP) and 30-hydroxy-5,6,7,40-tetramethoxyflavone (TMF). Furthermore, to identify possible mechanisms of action based on structure–activity relationships and molecular docking. The in vitro ACE inhibition activity relied on determining hippuric acid (HA) formation from ACE-specific substrate (hippuryl-histidyl-leucine (HHL)) by the action of ACE enzyme. A High Performance Liquid Chromatography method combined with UV detection was developed and validated for measurement the concentration of produced HA. The chelation ability of OS extract and its reference compounds was evaluated by tetramethylmurexide reagent. Furthermore, molecular docking study was performed by LeadIT-FlexX: BioSolveIT’s LeadIT program. OS ethanolic extract (OS-E) exhibited highest inhibition and lowest IC50 value (45.77 1.17 g/mL) against ACE compared to the other extracts. Among the tested reference compounds, EUP with IC50 15.35 4.49 g/mL had highest inhibition against ACE and binding ability with Zn (II) (56.03% 1.26%) compared to RA, TMF and SIN. Molecular docking studies also confirmed that flavonoids inhibit ACE via interaction with the zinc ion and this interaction is stabilized by other interactions with amino acids in the active site. In this study, we have demonstrated that changes in flavonoids active core affect their capacity to inhibit ACE. Moreover, we showed that ACE inhibition activity of flavonoids compounds is directly related to their ability to bind with zinc ion in the active site of ACE enzyme. It was also revealed that OS extract contained high amount of flavonoids other than RA, TMF, SIN and EUP. As such, application of OS extract is useful as inhibitors of ACE.